Industry-wide work rules and productivity: Evidence from Argentine union contract data - Carlos Lamarche (IZA Journal of Labor & Development, 2013)
In the early 1990's, the Argentine government promoted a framework for productivity-based negotiations between firms and unions at low levels of organization. The policy weakened the industry-wide collective bargaining system, which sets working conditions for all firms in an industry. This paper employs newly developed quantile regression approaches to investigate the effect of union practices on productivity within the context of the reform. The findings show that (i) industry-wide practices on displacement of workers and training have a negative impact on productivity; (ii) work practices do not appear to restrict economic efficiency in the post-reform period; (iii) union practices on technology acquisition have an adverse effect on high-productivity growth industries. Productivity seems to improve in an economy promoting policies to weaken industry-wide collective bargaining.
Keywords: J52; O14; O43; O54; 330; Work practices; Productivity; Manufacturing; Quantile regression